2019
DOI: 10.1101/652388
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial and fungal communities are differentially modified by melatonin in agricultural soils under abiotic stress

Abstract: An extensive body of evidence from this last decade indicates that melatonin enhances plant resistance to several biotic and abiotic stressors. This has led to an interest in the use of melatonin in agriculture to reduce negative physiological effects from environmental stresses that affect yield and crop quality. However, there are no reports regarding the effects of melatonin on soil microbial communities under abiotic stress, despite the importance of microbes for plant root health and function. Three agric… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
(108 reference statements)
1
4
0
Order By: Relevance
“…Here, two indexes (Chao 1 and observed species) for fungal communities and four indexes (Chao 1,observed species,Shannon and Simpson) for bacterial communities all showed significant differences among treatments, which implied that rhizospherically applied melatonin changed the richness of fungal communities and altered both richness and diversity of bacterial communities under low temperature. Similarly, exogenous melatonin alters the structure of soil bacteria and has a significant effect on bacterial alpha diversity under abiotic stress conditions (Madigan et al, 2019). In addition, exogenous melatonin reduces the Shannon diversity of bacterial community and reprograms the rhizosphere microbial community to modulate the responses of barley to abiotic stress (Ye et al, 2022), which is consistent with our findings.…”
Section: Rhizospherically Applied Melatonin Altered the Diversity Of ...supporting
confidence: 90%
“…Here, two indexes (Chao 1 and observed species) for fungal communities and four indexes (Chao 1,observed species,Shannon and Simpson) for bacterial communities all showed significant differences among treatments, which implied that rhizospherically applied melatonin changed the richness of fungal communities and altered both richness and diversity of bacterial communities under low temperature. Similarly, exogenous melatonin alters the structure of soil bacteria and has a significant effect on bacterial alpha diversity under abiotic stress conditions (Madigan et al, 2019). In addition, exogenous melatonin reduces the Shannon diversity of bacterial community and reprograms the rhizosphere microbial community to modulate the responses of barley to abiotic stress (Ye et al, 2022), which is consistent with our findings.…”
Section: Rhizospherically Applied Melatonin Altered the Diversity Of ...supporting
confidence: 90%
“…For example, melatonin treatment modulates the bacterial and fungal communities in agricultural soils under abiotic stress. This treatment even increases the populations of some microbes as indicated by the increased operational taxonomic units (OUT) which are suppressed under abiotic stress (150). Recently Madigan et al have also observed that high doses of melatonin application increase the abiotic stress tolerance to phytopathogenic fungi in an in vitro study (Melatonin Research, in press).…”
Section: Melatonin In Infectious Diseasesmentioning
confidence: 99%
“…Soils were sampled with the permissions of Rob Binks in Yaloak estate, Bullan, VIC, and Gary Clarke in Melbourne Polytechnic Farm, Yan Yean, VIC, Australia. This manuscript has been released as a Pre-Print at bioRxiv (Madigan et al, 2019).…”
mentioning
confidence: 99%